Thalweg and Ridge Network Extraction From Unaltered Topographic Data as a Basis for Terrain Partitioning. Issue 4 (15th April 2023) - Moretti, Giovanni; Orlandini, Stefano
Abstract: High‐resolution grid digital elevation models (DEMs) are increasingly used by scientists and engineers to describe the current state and evolution of Earth and planetary topography. These data, however, are commonly altered by depression filling and grid coarsening procedures. Alteration of observed topographic data may cause significant information loss and limit the capabilities of models. This study shows that physically meaningful thalweg and ridge networks can be extracted automatically from any unaltered high‐resolution grid DEM, and that these networks can be used as bases for terrain partitioning. The slopeline network connecting grid cell centers is used to identify ridge points as those grid cell border midpoints and vertices that are not crossed by slopelines. From each ridge point, the average length of the two slopelines extending on the opposite slopes of the ridge until they rejoin is then computed. Based on these lengths, exorheic and endorheic basins are identified. Thalwegs of exorheic and endorheic basins are finally connected through spilling saddles to form the thalweg network. The related ridge network is identified based on neighboring relationships between ridge points. Thalweg and ridge networks are hierarchized using the well‐known concept of drainage area and an extended concept of dispersal area to inform terrain partitioning at any level of detail. Observed topographic features are well reproduced by extracted networks. The impact of preserving depressions over mountain areas is evaluated, and the benefits from unstructured terrain partitioning based on thalweg and ridge networks in the description of flood plain inundation are illustrated. Plain Language Summary: Detailed topographic data are increasingly used by scientists and engineers to describe the current state and evolution of Earth and planetary topography. In current models, however, depressions are commonly filled for model simplicity, and grids are normally coarsened for computational efficiency. Alteration of observed topographic data may cause a significant information loss and limit the capabilities of models. In this study, it is shown that the lines following the lowest part of a valley or channel (thalwegs) and the lines of intersection at the top between opposite slopes (ridges) are the essential topographic features (bases) that need to be extracted from observed topographic data and retained when terrain is partitioned. New terrain analysis methods are developed to extract thalweg networks connecting depression (endorheic) and drainage (exorheic) basins, and to identify physically meaningful ridge networks. Observed topographic features are well reproduced by extracted networks. The impact of preserving depressions over mountain areas is evaluated, and the benefits from unstructured terrain partitioning based on thalweg and ridge networks in the description of flood plain inundation are illustrated. The developed methods provide a new pathway for scientists and engineers to rigorously incorporate detailed topographic data into their descriptions of Earth surface processes. Key Points: Physically meaningful thalweg and ridge networks can be extracted automatically from any high‐resolution grid digital elevation model Depressions and nested systems of exorheic and endorheic basins are handled without the need to alter the observed topographic data Thalweg and ridge networks can be obtained at the desired level of detail and are presented here as novel bases for terrain partitioning